Lycopene supplementation reduces TNF-alpha via RAGE in the kidney of obese rats - Pierine, D. T. [UNESP]; Navarro, M. E. L. [UNESP]; Minatel, I. O. [UNESP]; Luvizotto, R. A. M. [UNESP]; Nascimento, A. F. [UNESP]; Ferreira, A. L. A. [UNESP]; Yeum, K-J; Correa, C. R. [UNESP] (Nature Publishing Group, 2014)
The kidney is a target organ for injuries caused by advanced glycation end products (AGEs) in obesity. The receptor of AGEs (RAGE) is proinflammatory and appears to have a role in the pathogenesis of renal disease due to obesity.OBJECTIVE: The aim was to verify the effect of obesity on renal damage and the effect of lycopene on these complicationsDESIGN AND METHODS: Male Wistar rats were randomly assigned to receive a control diet (C, n = 7) or a high-fat diet plus sucrose (HD+S, n = 14) for 6 weeks. After this period, the HD+S animals were randomized into two groups: HD+S (n = 7) and HD+S supplemented with lycopene (HD+S+L, n = 7). The animals received maize oil (C and HD+S) or lycopene (HD+S+L) for a 6-week period.RESULTS: The HD+S and HD+S+L animals demonstrated insulin resistance (OGTT glucose after 150 min; C: 117.6 +/- 3.9 < HD+S: 138.1 +/- 5.1 = HD+S+L: 137.8 +/- 5.2 mg dl(-1); P = 0.01); however, no changes were seen in fasting glucose, plasma lipids, blood pressure or renal function. Renal concentrations of RAGE and TNF-alpha increased in the HD+S group and lycopene supplementation restored these to control group values (RAGE: C: 3.1 +/- 0.3 = DH+S+L: 3.1 +/- 0.3 < DH+S: 3.6 +/- 0.4 mu g g(-1); P = 0.014; TNF-alpha: C: 227.8 +/- 2.7 = DH+S+L: 227.4 +/- 2.2 < DH+S: 238.7 +/- 3.0 pg/ml; P = 0.014).CONCLUSIONS: Lycopene may be beneficial in the prevention and treatment of oxidative stress and inflammation in the kidney due to obesity.